MANPOWER PLANNING PRACTICES AND ORGANISATIONAL GROWTH: EVIDENCE FROM MTN NIGERIA, OWERRI - Euphemia Onyewuenyi, Chiamaka (African Journal of Social and Behavioural Sciences, 2026)
This study examined the influence of manpower planning practices on organisational growth using MTN Nigeria, Owerri, as a case study. The research focused on four dimensions of manpower planning: manpower forecasting, recruitment planning, development planning, and succession planning. The study was anchored on Human Capital Theory. A correlational survey design was adopted, and data were collected from 122 employees using two structured questionnaires—the Manpower Planning Practices Questionnaire (MPPQ) and the Organisational Growth Questionnaire (OGQ). Pearson correlation and simple linear regression were used for analysis at a 0.05 significance level. The findings revealed that manpower forecasting and development planning had strong positive relationships with organisational growth, while recruitment planning and succession planning showed moderate positive effects. The study concludes that effective workforce planning enhances organisational productivity and sustainability. It recommends that organisations strengthen workforce forecasting, structured recruitment, employee development, and leadership succession strategies.